The lord of the rings. The fellowship of the ring - Osborne, Barrie; Jackson, Peter, 1961-; Walsh, Fran, 1959-; Wood, Elijah, 1981-; McKellen, Ian.; Tyler, Liv.; Mortensen, Viggo, 1958-; Astin, Sean.; Blanchett, Cate, 1969-; Rhys-Davies, John.; Lee, Christopher, 1922-2015.; Tolkien, J. R. R. (John Ronald Reuel), 1892-1973.; et al. ([United States] : New Line Home Entertainment, 2002)
Elderly hobbit Bilbo Baggins relinquishes possession of a golden ring possessing magical powers to Frodo, his youthful heir. Charged with casting the ring into the fires from which it was forged, the young hobbit begins an arduous trek across Middle-earth, accompanied by a stalwart band including his best friend Sam, the mercurial wizard Gandalf, the warrior Aragorn, and the blustery Gimli, among others. Opposed by the treacherous sorcerer Saruman and the demonic emissaries of Sauron, the Dark Lord, this ever-embattled Fellowship makes its way slowly toward the dark land of Mordor.
Originally produced as a motion picture in 2001.
Based on the books by J.R.R. Tolkien.
Special features: Discs 1 & 2: four feature-length commentaries by the director and writers, the cast, the production and design teams, with more than 30 participants.
Special features: Disc 3: The appendices part one - From book to vision: six documentaries covering J.R.R. Tolkien, the process of adapting the book into a screenplay and planning the film, designing and building Middle-earth, as well as a visit to Weta workshop with an up-close look at costumes, weapons, armor, creatures and miniatures created for the film; an interactive map of Middle-earth tracing the journey of the Fellowship; galleries of art and accompanying slide shows with commentary by the artists; storyboards and previsualization sequences with film comparisons.
Special features: Disc 4: The appendices part two - From vision to reality: 11 original documentaries covering the cast, principal photography, a day in the life of a hobbit, visual effects, post production, editing, music and sound and the release of the film; galleries of behind-the-scenes photographs.
Director of photography, Andrew Lesnie ; editor, John Gilbert ; music, Howard Shore ; costume designers, Ngila Dickson ... [et al.] ; production designer, Grant Major.
Keywords: Baggins, Frodo -- Drama; Middle Earth (Imaginary place) -- Drama; Feature films; Fantasy films; Video recordings for the hearing impaired; Videos (DVD)